1997
DOI: 10.1080/00039899709602878
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Arsenic Excretion as a Biomarker of Arsenic Exposure in Children

Abstract: Urinary arsenic concentration has been used generally for the determination of exposure, but much concern has been raised over the most appropriate expression for urinary arsenic levels. In this study, we examined the influence of various adjustments of expressing urinary arsenic data. All children who were less than 72 mo of age and who were potty trained were invited to participate in the present study. Urine, soil, and dust samples were collected, and arsenic measurements were made. The geometric mean of sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
1
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 23 publications
1
19
1
2
Order By: Relevance
“…Normal As levels in urine vary from 5 to 40 μg per day (reference, 1.5 L urine per day). We decided not to adjust the As levels in urine to creatinine values, as it has been proved to be influenced by many factors (i.e., age, sex, race/ethnicity, diet, exercise) and it could therefore complicate the study, as other researchers previously reported (Hwang et al 1997;Barr et al 2005;Gamble and Liu 2005;Steinmaus et The differences between native and immigrant children were significant regarding to MMA (p = 0.008) and DMA (p = 0.006), not significant regarding total As in urine and hair and marginally significant regarding to total As in nails (p = 0.065).The differences between native and immigrant children from Bangladesh were significant regarding to MMA (p = 0.031) and DMA (p = 0.009) and total As in nails (p = 0.006). Parentheses: values of the standard deviation.…”
Section: Discussionmentioning
confidence: 96%
“…Normal As levels in urine vary from 5 to 40 μg per day (reference, 1.5 L urine per day). We decided not to adjust the As levels in urine to creatinine values, as it has been proved to be influenced by many factors (i.e., age, sex, race/ethnicity, diet, exercise) and it could therefore complicate the study, as other researchers previously reported (Hwang et al 1997;Barr et al 2005;Gamble and Liu 2005;Steinmaus et The differences between native and immigrant children were significant regarding to MMA (p = 0.008) and DMA (p = 0.006), not significant regarding total As in urine and hair and marginally significant regarding to total As in nails (p = 0.065).The differences between native and immigrant children from Bangladesh were significant regarding to MMA (p = 0.031) and DMA (p = 0.009) and total As in nails (p = 0.006). Parentheses: values of the standard deviation.…”
Section: Discussionmentioning
confidence: 96%
“…However, this assumption has not been validated, and no clear standards exist for correction for urine volume, contaminant excretion, dilution, or time between exposure and void (Hwang et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Biomarker data have been collected for children to evaluate environmental exposures to lead (56), benzene (57), arsenic (58), chromium (59)(60)(61), and pesticides (62,63). Most recently, the Minnesota NHEXAS children's pesticide exposure study collected urine samples from children on three alternate days and analyzed them for metabolites of chlorpyrifos, malathion, atrazine, and diazinon.…”
mentioning
confidence: 99%